Meanings of Reconciliation in the School Context - Burridge, Nina (The Australian Journal of Indigenous Education, 2006)
Abstract This paper draws on findings from a major research project conducted between 1998 and 2000 on meanings of reconciliation in the school education sector. Using data collected from surveys and drawing from the community context in which schools exist, it explores and analyses meanings of reconciliation within school communities when the discourse of what constitutes reconciliation was at its peak. Survey responses were used to map the level of support for reconciliation and to identify what barriers existed to the teaching of reconciliation in schools. Responses were categorised into various themes which defined the type of meaning respondents had accrued to reconciliation. The overwhelming impression from this research is that Aboriginal and non-Aboriginal people aspire to a level of harmonious co-existence; what is less clear is the direction on how this can be achieved. There is a great level of support for reconciliation within the education community with almost no responses being overtly negative. Many of the comments can be seen as reflecting “soft” reconciliation perspectives. A prevailing theme of this research is that the harder issues of reconciliation are being ignored in favour of symbolic representations. What perhaps best distinguished the survey comments from the responses from the general community was the greater desire amongst the education sector for equitybased solutions and the need to redress past injustices through social justice action. There was a greater understanding of the link between past dispossession and current disadvantage and this required action through specific programmes, and education was seen as a major part of this. Given the current sociopolitical context, anecdotal indications suggest that reconciliation may reflect wider community attitudes and may be “off the agenda” in schools, except within the narrow parameters of Department of Education requirements for activities or celebrations during NAIDOC or Reconciliation weeks.